Portuguese Democratisation 40 Years on: Its Meaning and Enduring Legacies - Lobo, Marina Costa (2016)
On the fortieth anniversary of the Carnation Revolution, it is pertinent to ask how Portuguese citizens understand their transition to democracy. In this article, some of the main findings concerning the meanings and legacies of 25 April 1974 are presented, drawing on the findings of two surveys focusing on Portuguese attitudes towards 25 April and fielded in 2004 and 2014, respectively, to a representative sample of the Portuguese population. Here we focus on the degree to which the transition is viewed positively and its social and economic legacies. In the final sections, the main findings of the articles in this special issue are discussed through a presentation of the main questions they answer and the new ones they raise.